PENGARUH PROFESIONALISME GURU PAI DAN PENGELOLAAN KELAS TERHADAP PENINGKATAN MUTU PENDIDIKAN SEKOLAH MENENGAH PERTAMA (SMP) NEGERI 2 PLUMBON KECAMATAN PLUMBON KABUPATEN CIREBON - Dafiah, Dafiah (Pascasarjana IAIN Syekh Nurjati Cirebon, 2016)
PAI teachers of SMP Negeri 2 Plumbon was not professional but the educational quality was good, those most of students graduated of elementary school were enthusiasticed and registered to SMP Negeri 2 Plumbon. From this problem, the research has been intended to find out how many influences of the professionalism PAI teachers and classes management to increase educational quality of SMP Negeri 2 Plumbon. So what are the good established educational quality of SMP Negeri 2 Plumbon. The purpose from this research is to find out the influencence of the professionalism PAI techer and classes management to increase educational quality. The consideration design of research where the professionalism PAI teachers are good regarding to increase educational quality will be good too viceversa. An approachment from this thesis research uses quantitative method. The instrument for collecting data are observations, interviews, documentation studies, literature riviews and questionnaires to all of teachers of SMP Negeri 2 Plumbon there are 43 teachers. In this research, the researcher uses population research because the subject less than much. Therefore in this research, a population as a sample. The finding of the research showed that the professionalism of PAI teachers in SMPN 2 Plumbon and classes management were not significant influencing to increase educational quality SMPN 2 Plumbon, it is related from risult of variable influencing X1 and X2 on Y just of a fit enough levels is 0,29 by contribution 8,4%.Â Key word: professional teacher, classroom management and quality of educationÂ